2021
DOI: 10.1111/aogs.14112
|View full text |Cite
|
Sign up to set email alerts
|

Performance of antenatal imaging to predict placenta accreta spectrum degree of severity

Abstract: Introduction In cases of placenta accreta spectrum, a precise antenatal diagnosis of the suspected degree of invasion is essential for the planning of individual management strategies at delivery. The aim of this work was to evaluate the respective performances of ultrasonography and magnetic resonance imaging for the antenatal assessment of the severity of placenta accreta spectrum disorders included in the database. The secondary objective was to identify descriptors related to the severity of placenta accre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…Our results complement several other studies that reported bladder wall interruption and uterovesical interruption as predictors of a worse outcome in PAS patients [ 24 , 40 ]. In the case of MR imaging, similar percretization descriptors to those used in our study were associated with adverse events in several studies investigating PAS.…”
Section: Discussionsupporting
confidence: 91%
“…Our results complement several other studies that reported bladder wall interruption and uterovesical interruption as predictors of a worse outcome in PAS patients [ 24 , 40 ]. In the case of MR imaging, similar percretization descriptors to those used in our study were associated with adverse events in several studies investigating PAS.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, this can explain why the performance of ultrasound and magnetic resonance imaging to discriminate mild from severe PAS disorders remains poor. 87 Over 90% of cases of PAS are found in women with a prior CD presenting with a placenta previa. 65e67 However, cases of PAS have been described in primigravida women with no surgical history but presenting with a uterine pathology, such as a bicornuate uterus, adenomyosis, submucous fibroids, or myotonic dystrophy, 65 and as found in our systematic review, after radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In 385 women (87.1%) the diagnosis of PAS was made antenatally by ultrasound or MRI. Imaging details are published separately 17 . Imaging experts scored the likelihood that significant PAS was present at the time of imaging in 414 women (0 = unlikely, 10 = very likely) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Expert antenatal imaging can accurately predict PAS. Despite expertise, minor forms of PAS are difficult to distinguish from severe PAS, leading to the possibility of false‐positive diagnoses 17 . The advantage of delivering in a referral center in these cases may be that conservative management can be offered more confidently, and hysterectomy can be avoided in false‐positive cases and, when necessary, may be completed with fewer complications.…”
Section: Discussionmentioning
confidence: 99%